BS ISO 4586-4. High-pressure decorative laminates (HPL, HPDL). Sheets based on thermosetting resins (usually called laminates). Part 4. Classification and specifications for compact laminates of thickness 2 mm and greater (10th March 2020) - British Standards Institution,
No abstract available